Design Of Molecular Configuration Of Polyimide Nanocomposite Membrane For Co2 N2 Separation - Tan, Peng Chee (2019)
The application of polyimide (PI) membrane for industrial carbon dioxide (CO2) removal has been restricted by its intrinsic trade-off between permeability and selectivity. In view of this, this study explores the molecular design of PI polymer and the development of PI/zeolitic imidazolate framework-8 (ZIF-8) nanocomposite membrane aiming to improve the gas separation performance. Principally, the molecular weight of polyamic acid (PAA) and its corresponding PI depend strongly on the monomer reactivity, which is dominantly controlled by the steric hindrance of monomers’ substituent instead of their electronic nature. It was also found that the rheological behavior and molecular weight of PAA could act as a guideline to screen the suitable membrane synthesis protocol for a particular PI structure. Specifically, a PAA with high viscosity (> 81 cP) and high molecular weight (≥ 5.39 Mg/mol) is the prerequisites in forming a defect-free PI membrane via casting of chemically imidized PI solution. It was found in this work that the synergistic effect of both atomic configuration and polarity of monomer needs to be taken into consideration in analyzing the fractional free volume (FFV) of a PI membrane. A monomer with non-planar structure and low polarity is highly preferable to attain a PI membrane with high FFV. 4,4′-(hexafluoroisopropylidene)diphthalic anhydride (6FDA)-2,4,6-trimethyl-m-phenylenediamine (DAM):3,5-diaminobenzoic acid (DABA) (3:2) membrane with a high FFV of 0.212 showed the best separation performance among the PI structures studied. It possessed a CO2 permeability of 63 Barrer (0.60 GPU) and CO2/N2 selectivity of 57 at 3 bar of permeation test. Molecular dynamics (MD) simulation was also performed to predict the gas transport behavior of PI membrane. Indeed, the reliability of the PI model developed using Materials Studio software was validated as the predicted CO2 and N2 permeability only differed from the experimental results by a factor of 1.86 and 1.76, respectively. Later, ZIF-8 particles were deposited on top of the alumina-supported PI membrane via dip-coating to produce PI/ZIF-8 nanocomposite membrane. The effectiveness of (3-aminopropyl)-triethoxysilane (APTES) in improving the compatibility between alumina-PI-ZIF-8 was predicted using molecular simulation based on the binding energy. The simulation result was also further verified experimentally. In binary gas separation, an optimum CO2 permeance and CO2/N2 selectivity were found at 93.47 GPU and 7.50, respectively at 5 times of ZIF-8 dip-coating. In overall, this work provides a fundamental insight into the role of molecular design and PI/ZIF-8 nanocomposite membrane in tailoring the membrane gas separation performance. Future research can be focused on the surface modification of ZIF-8 to minimize the tendency of ZIF-8 agglomeration and hence further improve the gas separation performance of PI/ZIF-8 nanocomposite membrane.